Influence of CuO nanoparticles in enhancing the overall heat transfer around a square cylinder - Bouakkaz, Rafik; Khelili, Yacine; Abdelouahed, Aliouali (Metallurgical and Materials Engineering, 2019)
In this study, steady flow and heat transfer through a copper-water nanofluid around a square cylinder was investigated numerically by using a finite-volume method for Reynolds numbers of 10-40. Furthermore, the range of nanoparticle volume fractions () considered is 0 â‰¤ â‰¤ 0.04, with three different nanoparticle diameters dnp = 30, 60 and 90 nm. The variation of the local and the average Nusselt numbers with Reynolds number, and volume fractions are presented for the range of above conditions. The averaged Nusselt number showed clear enhancement comparing with the base fluids. This enhancement is more apparent in flows with higher particle volume concentration, whereas the particle diameter imposes an opposing effect on the heat transfer characteristics.